Japan Decides 2021 The Japanese General Election - Pekkanen, Robert J.; Reed, Steven R.; Smith, Daniel M. (Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
XXVI, 400 p. 49 illus., 2 illus. in color.